An ultra-sensitive dual-mode imaging system using metal-enhanced fluorescence in solid phantoms - Barnoy, Eran A. (Nano Res, 2015)
In this study we developed a highly sensitive dual modal imaging system designed for gold nanoparticles (GNPs) conjugated to various fluorophores in solid phantoms. The system consists of fluorescence lifetime imaging microscopy (FLIM) for surface imaging, diffusion reflection (DR) for deep tissue imaging (up to 1cm), and metal enhanced fluorescence (MEF). We detected quenching in fluorescent intensity (FI) for the conjugation of gold nanospheres (GNS) as well as gold nanorods (GNRs) to Fluorescein, which has an excitation peak at a wavelength shorter than the surface plasmon resonance (SPR) of both types of GNPs, and enhanced FI in conjugation to Rhodamine B and Sulforhodamine B, both with excitation peaks in the GNPs' SPR. The enhanced FI was detected in solution as well as in solid phantoms from FLIM measurements. DR measurements detected GNR presence within the solid phantoms by recording dropped rates of light scattering using wavelengths corresponding to the GNRs' absorption. With the inclusion of MEF, this promising dual modal imaging technique enables efficient and sensitive molecular and functional imaging.